CERPEN âWARA<<`A AL-GAIBIâ DALAM ANTOLOGI QAT{ARA<TUN MIN AD-DUMU<âI KARYA SAMI<RAH BINTU AL-JAZI<RAHAL-âARABIYYAH: ANALISIS STRUKTURAL âSTANTONâ - , MUSTIKA QADAR ANGGRAENI; , Mahmudah, S.S., M.Hum. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
âWara>`a al-Gaibiâ is a short story written by Sami>rah bintu al-Jazi>rah al- âArabiyyah. This short story begins with friendship of âIâ that is a man and Ah}mad. Through I character, love story between Ah}mad and Dunya> be told. Dunya> is a beautiful woman who is trying to marry again with Ah}mad after her husband died but obstructed by a will that complicates Dunya> to marry again. The short stories essentially is a structure that consists of elements which are inter-related. Therefore, the short story will be analyzed using a structural theory. Structural theory that used in this thesis is a structural theory of Robert Stanton. Research carried out by outlining the intrinsic elements of the theme, the facts of the story, and literary means. The fact the story to be described is the characters, plot, and setting, while the literary means restricted point of view and the title only. A theme that is contained in short stories is personâs plan does not equal to Godâs will. The principal character in short stories is Ah}mad, while Dunya> and âIâ as a figure additional. For the other characters generally do not have a significant role. The plot in this short story presented chronologically, sort of the beginning to the end of the story. The background of a place in this short story, it was I characterâs home, the home near I characterâs home , and the Ah}madâs office. As for the setting of the time is the time people running their daily lives such as at the time of the evening, while the social background namely upper middle class social life. Point of view in the short story is a first person perspective sideline. Title on short stories is based on a theme. Relation between element of the intrinsic contained in the short story was seen on the relation of the theme with the character and the theme with the title. The result showed short story of âWara>`a al-Gaibiâ has links among elements intrinsic support each other and form a structure that generates meaning intact.